A study of the actual and potential usage of information and communication technology at district and provincial levels in Mozambique with a focus on the health sector - Braa, Jørn; Macome, Esselina; Mavimbe, João Carlos; Nhampossa, José Leopoldo; da Costa, João Leopoldo; José, Bonifacio; Manave, Aurélia; Sitói, António (The Electronic Journal of Information Systems in Developing Countries, 2001)
This article presents results from a study on the use and appropriation of information and communication technologies (ICT) in Mozambique with a focus on the health sector. The three provinces of Gaza, Inhambane and Niassa were surveyed and two questionnaires addressing 1) computer users and their ability to manage ICT, and 2) health workers and their handling of health information, were used. Based on this study appropriate strategies for developing an ICT-infrastructure with the needs of the health sector as points of departure are discussed. The study is born out of a program to strengthen and further develop the health information and management systems at district and provincial levels as part of a process to support decentralisation of the health system in Mozambique. The study shows that computers and Internet are rapidly being spread to the provincial capitals and major districts in Mozambique. A main problem identified is the lack of ICT-skills and education and poorly developed infrastructure and networks of support. There are very few formal ICT companies providing hardware, and even less, software support. Maintenance and learning about ICT are to a large extent going on within informal networks of computer users in the provinces. A main finding in this study is that development of ICT capacity and information systems at district and provincial levels in Mozambique needs to be an integrated effort across sectors. A district health information system cannot be developed in a void. A general recommendation is to develop educational programmes ranging from training of ICT entrepreneurs and health workers and managers, to Masters and PhD programmes in ICT and health information systems. A specific recommendation related to health information systems development is to focus on the district level and to develop a strategy which encompasses and integrates all districts, both the advanced districts with computers and the majority of the districts where there are no computers.
Keywords: *indexed; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; health - health information systems / saúde - sistema de informação de saúde; health / saúde

Outcome Mapping: Building Learning and Reflection into Development Programs - Earl, Sarah; Carden, Fred; Smutylo, Terry (IDRC, 2001)
More and more, development organizations are under pressure to demonstrate that their programs result in significant and lasting changes in the well-being of their intended beneficiaries. However, such "impacts" are often the product of a confluence of events for which no single agency or group of agencies can realistically claim full credit. As a result, assessing development impacts is problematic, yet many organizations continue to struggle to measure results far beyond the reach of their programs. Outcome Mapping recognizes that development is essentially about people relating to each other and their environment. The originality of this approach lies in its shift away from assessing the products of a program to focus on changes in behaviour, relationships, actions, and activities in the people, groups, and organizations it works with directly. In doing so, Outcome Mapping debunks many of the myths about measuring impact. It will help a program be specific about the actors it targets, the changes it expects to see, and the strategies it employs and, as a result, be more effective in terms of the results it achieves. This publication explains the various steps in the outcome mapping approach and provides detailed information on workshop design and facilitation. It includes numerous worksheets and examples.
Keywords: *tagged; L - english / inglês; M - evaluation / avaliação; M - methodology / metodologia

The Indonesian Financial Crisis: From Banking Crisis to Financial Sector Reforms, 1997-2000 - Sharma, Shalendra D. (Cornell University Press, 2001)
In mid-1998, a World Bank study grimly noted that "Indonesia is in deep economic crisis. A country that achieved decades of rapid growth, stability, and poverty reduction is now near economic collapse . . . no country in recent history, let alone one the size of Indonesia, has ever suffered such a dramatic reversal of fortune." There is bitter irony in Indonesia's fall from grace. Long hailed as a model of successful economic development, it was widely predicted to escape the fate of Thailand. Between June-August 1997, as Thailand's economy unraveled and the virulent Asian flu sent shock waves through the region, the Indonesian economy remained relatively stable—a veritable rock in the stormy sea. Even the World Bank remained upbeat about the short-term outlook, believing that a widening of the intervention band would be sufficient to ward off contagion.4 The Indonesian government, which received much praise for its swift and decisive response to the crisis, went to great lengths to assure jittery investors "that Indonesia was not Thailand." Then the unthinkable happened. Indonesia suddenly succumbed to the contagion, and, measured by the magnitude of currency depreciation and contraction of economic activity, it emerged as the most serious casualty of Asia's financial crisis. What happened? Why did Indonesia (and the other high-performing Asian economies) collapse like hollow dominoes? In the numerous post-mortems that have followed, analysts have identified a number of related factors behind the region's dramatic reversal of fortune. In the case of Indonesia, the variable that soon acquired particular salience was "crony capitalism." Initially popularized by the Economist, the term quickly took a life of its own. Soon thereafter, the distinguished MIT economist, Paul Krugman, would argue that crony capitalism lay the root of Indonesia's—and indeed, East Asia's—financial woes. Krugman describes the innerworkings and manifestations of the insidious crony capitalism in evocative prose.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico